Peran Guru PAI dalam Membangun Pendidikan Karakter dalam Pembelajaran Fiqh - Eva Safitri; Ida Laila; Srinanda; Muhammad Yasin (Universitas Muhammadiyah Prof Dr Hamka, 2024)
Islamic Education (PAI) teachers play a crucial role in shaping the character and ethics of young Muslim students through the teaching of fiqh. Efforts that can be made by PAI teachers to build moral human resources (HR) among students at Pesantren Al-Qur’an Sangatta Taqwa include teaching Islamic values, providing personal and social guidance, implementing fiqh in daily life, setting examples of Islamic behavior, developing moral skills, involving parents, and conducting evaluation and feedback. Supporting factors in character formation at Pesantren Al-Qur’an Sangatta Taqwa include teaching Islamic values based on fiqh and providing personal and social guidance. On the other hand, inhibiting factors include the influence of secular environments and socio-economic influences. This study employs a qualitative approach with a descriptive type, involving PAI teachers and young Muslim students as research subjects. The results of the study are expected to provide practical guidance for PAI teachers and educators in their efforts to enhance the ethics of young students. The purpose of this study is to understand the role of PAI teachers in building character education through the teaching of fiqh at Pesantren Al-Qur’an Sangatta Taqwa, which can be seen based on the efforts made by PAI teachers to develop ethical human resources (HR) at Pesantren Al-Qur’an Sangatta Taqwa and to identify the supporting and inhibiting factors in character formation among students at Pesantren Al-Qur’an Sangatta Taqwa.